The Mediating Role of Conceptions of Learning in the Relationship Between Metacognitive Skills/Strategies and Academic Outcomes Among Middle-School Students - Vettori, Giulia; Vezzani, Claudio; Bigozzi, Lucia; Pinto, Giuliana (Frontiers in Psychology, 2018)
The present study investigated the mediating role of conceptions of learning in the relationship between metacognition and academic outcomes among middle school students. The self-report ‘Learning Conceptions Questionnaire’ (LCQ) and ‘Metacognitive questionnaire on the method of study’ (QMS) were administered to 136 middle school students and their academic outcomes were collected. Correlation analyses revealed that within metacognition only self-assessment was positively correlated with academic outcomes. Mediation analysis indicated that a conception of learning as internal attribution of success and failure was significantly involved as mediator in the relationship between metacognition and academic achievements. The present study permitted to advance our knowledge about the relationship between metacognition and academic achievements and it opened the way to practical implications.